The Danish national return-to-work program – aims, content, and design of the process and effect evaluation - Aust, Birgit; Helverskov, Trine; Nielsen, Maj Britt D.; Bjorner, Jakob Bue; Rugulies, Reiner; Nielsen, Kent; Sørensen, Ole Henning; Grundtvig, Gry; Andersen, Malene F.; Hansen, Jørgen V.; Buchardt, Helle L.; Nielsen, Lisbeth; et al. (Scandinavian Journal of Work, Environment & Health, 2012)
The Danish national return-to-work (RTW) program aims to improve the management of municipal sickness benefit in Denmark. A study is currently ongoing to evaluate the RTW program. The purpose of this article is to describe the study protocol. The program includes 21 municipalities encompassing approximately 19 500 working-age adults on long-term sickness absence, regardless of reason for sickness absence or employment status. It consists of three core elements: (i) establishment of multidisciplinary RTW teams, (ii) introduction of standardized workability assessments and sickness absence management procedures, and (iii) a comprehensive training course for the RTW teams. The effect evaluation is based on a parallel group randomized trial and a stratified cluster controlled trial and focuses on register-based primary outcomes – duration of sickness absence and RTW – and questionnaire-based secondary outcomes such as health and workability. The process evaluation utilizes questionnaires, interviews, and municipal data. The effect evaluation tests whether participants in the intervention have a (i) shorter duration of full-time sickness absence, (ii) longer time until recurrent long-term sickness absence, (iii) faster full RTW, (iv) more positive development in health, workability, pain, and sleep; it also tests whether the program is cost-effective. The process evaluation investigates: (i) whether the expected target population is reached; (ii) if the program is implemented as intended; (iii) how the beneficiaries, the RTW teams, and the external stakeholders experience the program; and (iv) whether contextual factors influenced the implementation. The program has the potential to contribute markedly to lowering human and economic costs and increasing labor force supply. First results will be available in 2013. The trial registrations are ISRCTN43004323, and ISRCTN51445682.
Keywords: Denmark; design; economic evaluation; effect evaluation; evaluation; intervention; long-term sickness absence; organizational change; process evaluation; return to work; return-to-work; RTW; sickness absence; work resumption